2014
DOI: 10.1111/jsap.12211
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of positive pressure ventilation in 58 dogs: indications, prognostic factors and outcome

Abstract: The PaO2 /FiO2 ratio is an early prognostic indicator of successful weaning in dogs undergoing positive pressure ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…The minor role that pneumonia played in the cats herein is in line with the findings in a previous study where no instances of aspiration pneumonia were reported in dogs or cats undergoing MV for elapid snake envenomation . Pneumothorax, reported to occur in 3–29% of dogs or cats ventilated for different reasons, was not reported in any of the cats in this study, possibly indicating that aggressive ventilator settings with high peak pressure were not required in these animals …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The minor role that pneumonia played in the cats herein is in line with the findings in a previous study where no instances of aspiration pneumonia were reported in dogs or cats undergoing MV for elapid snake envenomation . Pneumothorax, reported to occur in 3–29% of dogs or cats ventilated for different reasons, was not reported in any of the cats in this study, possibly indicating that aggressive ventilator settings with high peak pressure were not required in these animals …”
Section: Discussionmentioning
confidence: 64%
“…Compared to dogs, cats are reported to have worse ventilator weaning rates when undergoing MV for any reason, with ventilator weaning rates for cats ranging from 15% to 25% and, for dogs, from 44% to 45% . This has been attributed to the smaller size of cats that could make MV and monitoring technically more challenging .…”
Section: Discussionmentioning
confidence: 99%
“…VAP is infrequently reported in the veterinary literature 6–10 . Previously reported cases of VAP have utilized radiographic changes or positive airway cultures for this diagnosis 6–10 . Two veterinary studies have defined VAP as pneumonia developing 48 hours after initiation of MV 7,10 .…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, an attempt to utilize a stricter definition of VAP that either excludes or better documents the extent of baseline disease in veterinary patients does not exist. Moreover, an attempt to utilize a broader set of criteria for the diagnosis of VAP, similar to that utilized in people, has yet to be made 6–10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation